Peripartum pubic symphysis separation – Current strategies in diagnosis and therapy and presentation of two cases. Issue 6 (June 2015) - Herren, C.; Sobottke, R.; Dadgar, A.; Ringe, M.J.; Graf, M.; Keller, K.; Eysel, P.; Mallmann, P.; Siewe, J.
Abstract: Background: During spontaneous vaginal delivery, pubic symphyseal widening is normal. Common changes are reversible after complication-free birth. However, cases of peripartum symphysis separation are rare. There is no consensus in the literature on how to treat pregnancy-related pubic symphysis separation. Methods: This review used a literature-based search (PubMed, 1900–2013) and analysis of 2 own case reports. Studies with conclusions regarding management were particularly considered. Results: Characteristic symptoms, suprapubic pain and tenderness radiating to the posterior pelvic girdle or lower back, may be noted 48 h after delivery. Pain on movement, especially walking or climbing stairs, is often present. Conservative treatments, such as a pelvic brace with physiotherapy and local interventions such as infiltration, are successful in most cases. Symptom reduction within 6 weeks is the most common outcome, but can take up to 6 months in some cases. Surgical intervention is needed in cases of persistent separation. Anterior plate fixation is offered as a well-known and safe procedure. Minimally invasive SI joint screw fixation is required in cases of combined posterior pelvic girdle lesions. Summary: Postpartum symphyseal rupture can be indicated with the rare occurrence of pelvic pain post-delivery, with sciatica or lumbago and decreased mobility. The diagnosis is made on clinical findings, as well as radiographs of the pelvic girdle. Conservative treatment with a pelvic brace is the gold standard in pre- and postpartum cases of symphysis dysfunction.